Grammedessa, a new genus of Edessinae (Hemiptera: Heteroptera: Pentatomidae) - Correia, Andre Oliveira; Fernandes, Jose Antonio Marin (Zootaxa, 2016)
The new genus Grammedessa is here proposed for 12 species: Edessa pallicornis, E. bugabensis, E. rorativentris and E. stillativentris, and eight new species: Grammedessa brunneotarsata, G. polytreta, G. flavolimbata, G. paraensis, G. braziliana, G. hypsolineata, G. multicavata and G. matogrossensis. Species belonging to this genus share four black punctured longitudinal stripes on the dorsal surface of the head; humeral angles laterally projected and slightly flattened dorso-ventrally; metasternal process with branches of anterior bifurcation narrow, long, and with acute apices; abdominal trichobothria placed laterally, not aligned with spiracles; females with gonocoxites 8 and laterotergites 8 always punctured, gonocoxites 8 large, subequal in length to laterotergites 9; males with ventral rim of pygophore deeply excavated, superior process of genital cup partially fused to the wall. Edessa strigiceps is considered a junior synonym of Grammedessa pallicornis n. comb.. Males of Grammedessa bugabensis n. comb. and Grammedessa rorativentris n. comb. are described for the first time. New distribution records of Grammedessa bugabensis, Grammedessa rorativentris, and Grammedessa stillativentris n. comb. is extended. The lectotype of Edessa bugabensis is herein designated.